2007
DOI: 10.1097/01.mpa.0000240607.49183.7e
|View full text |Cite
|
Sign up to set email alerts
|

Does Moderate Celiac Axis Stenosis Identified on Preoperative Multidetector Computed Tomographic Angiography Predict an Increased Risk of Complications After Pancreaticoduodenectomy for Malignant Pancreatic Tumors?

Abstract: There seems to be no evidence of an increased risk of postoperative or perioperative complication in patients undergoing the Whipple procedure, with a celiac stenosis of up to 60%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…This was consistent with significant interindividual variations of the duct system in the pancreatic head 11,12. However, surgeons might expect a clear frontal plane even based on PP immunohistochemistry of adult materials 4,7,8.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This was consistent with significant interindividual variations of the duct system in the pancreatic head 11,12. However, surgeons might expect a clear frontal plane even based on PP immunohistochemistry of adult materials 4,7,8.…”
Section: Discussionsupporting
confidence: 76%
“…Identification of the dorsal and ventral primordia of the pancreas, using adult as well as fetal materials, had been conducted with the aid of pancreatic polypeptide (PP) immunohistochemistry4-8 and the results provided a concept of segmentectomy for benign tumors in the pancreatic head 9,10. However, in contrast to the detailed studies of the pancreatic duct system,11,12 the arterial configuration was not investigated in the context of the pancreatic primordia or segments except for Sakamoto, et al4 possibly because of no basic embryologic study on arterial development of the pancreatic head. Consequently, in combination with studies using PP immunohistochemistry, the present study was aimed to describe development of the vascular topographical anatomy at and around the pancreatic head in order to provide a better understanding of the "segmental" treatment in pancreatic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The role of interventional vascular techniques for coeliac axis obstruction prior to PD in reducing postoperative complications is controversial for low-grade lesions, but have clear indications for lesions with >60% stenosis 16. Endovascular stents are used preoperatively to avoid technical challenges and potential morbidity associated with performing a vascular bypass at the time of PD 4 14 15.…”
Section: Discussionmentioning
confidence: 99%
“…However, predicting which patients will develop clinically relevant ischaemia following PD is challenging due to the highly variable nature of the collaterals that develop; this is an ongoing area of research 7. Smith et al 16 found no association between coeliac occlusion and increased postoperative morbidity when they analysed patients with <60% stenosis. Yet, in at-risk patients with radiographic evidence of high-grade coeliac stenosis with development of retrograde flow through the CHA, preoperative endovascular approach is a necessary intervention 4…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al reported that stenosis of <60%, as seen on CT, was not associated with an increased risk of postoperative or perioperative complications in patients undergoing PD. 4) The extreme variability of pancreatic and peripancreatic collateral vascularization and the common existence of collateral pathways from the dorsal pancreatic artery or from a replaced right hepatic artery may explain why hepatic blood flow can be maintained even after divisions of the GDA in cases of CA stenosis or occlusion. Ouaissi et al mentioned that decompression procedures were not necessary for patients with arterial stenosis of <50% before or during PD, while stenosis >50% needed treatment by revascularization surgery and/or endovascular stenting.…”
mentioning
confidence: 99%